Strategic Review: The CZTS Thin-Film Using Tandem and Multi-Junction Solar Cell - Saif Adnan Muhamad; Methaq Hadi Lafta (Advances in Engineering and Intelligence Systems)
In this study, a strategic review of fabrication technology and the CZTS (Cu2ZnSnS4) thin film solar cell using tandem and Multijunction structures is discussed. This review is tried to cover all the contents with a simple expression and at the same time so that the reader with any scientific level of this research field can have a good understanding of the research field and the importance of solar cells. Currently, two technologies are dominant in making solar cells (first and second generation) and new technology is in the research phase (third generation). The first-generation technology is based on silicon wafers with a thickness of 300μm - 400μm. The second generation of technology or thin-film technology, based on the semiconductor coating layer on glass, metal, or polymer layers, is 1μm - 5μm thick. Third-generation solar cells are also in the research phase, which includes nanocrystalline solar cells (based on liquid crystals), polymer solar cells, organic solar cells, perovskite solar cells (lead-mineral-organic hybrids or materials based on tin halides), Color Sensitive Solar Cells, Photo Electro Chemical Solar Cells, Multijunction Cells, Quantum Well Solar Cells, and Quantum Point Solar Cells. Although research into production technologies, especially third-generation technology, has evolved rapidly, there is still no review of the structures and results of all-generation technology. Due to the content of CZTS thin cells, the density of defects is an important role in the number of photovoltaic properties of the solar cell, many of these defects reduce the efficiency of the cell, and suggestions for increasing the efficiency of CZTSxSe1-x solar cells is introduced.